Additive manufacturing of electrochemical systems and their application in bioelectronic medicine - Sanjuan Alberte, Paola (2019)
Bioelectronic medicine is a growing field where a combination of electronic and biological systems are used to induce a therapeutic response. Despite the advancements achieved in the area with the production of retinal and cochlear implants, vagus nerve stimulators and wearable biosensors, there are some challenging limitations, including a poor integration in the bioelectronic interfaces and low specificity of the outputs. In order to solve this, additive manufacturing and electrochemical approaches are explored in this work. Bioelectronic interfaces were produced in situ, growing silver microwires between CHO cells, offering an example of engineering of seamless functional interfaces controlled remotely. A model of wireless intracellular bioelectronic communication was also provided, where gold nanoparticles (AuNPs) conjugated with a redox-dependent fluorescent porphyrin were used as intracellular transducers, reducing the typical invasiveness of electronic systems and converting electronic inputs into a fluorescent output when an external electric field was applied. The last part of the investigation was to create conductive polymeric scaffolds fabricated by two-photon polymerisation (2PP) with nano- and micro-topographies to provide mechanical and electrical cues to human induced pluripotent stem cells-derived cardiomyocytes and advance their in vitro maturation state.